Analisis Senyawa L-arginine pada Bawang Putih Tunggal dan Black Garlic Tunggal Dengan Menggunakan Metode HPLC (High Performance Liguid Chromatography) - Setiawan, Abdul Aziz; Nesha, Tafriani Sucianti; Pratiwi, Dina (Indonesian Research Gateway, 2017)
L-Arginine is a semi essential amino acid and has a function in arterial vascular relaxation and improves blood flow. Single-bulb black garlic was produced from ordinary single-bulb garlic clove by process from maillard browning at temperature at 700C and 95Y of humidity controlled room for a month. It is known that single-bulb black garlic has benefits as antidiabetes, uric acid, cholesterol, hypertension, endurance and others. This study aims to determine the content of L-Arginine compound on single-bulb garlic and single-bulb black garlic by using HPLC (High Performance Liguid Chromatography)method.The mobile phase used consists of buffer A and buffer B. Buffer A consists of Na-Acetate (pH 6.5), Na-EDTA, Methanol, and Tetrahidrofuran. While B buffer consists of Methanol and Water Pro Injection. Thermo Scientific Column ODS-2 Hyersil C18, flow rate 1 ml / min, using Flouresensi detector with 350 nm wavelength. Based on the results obtained L-Arginine compound contained in a single-bulb garlic of 2.504 while for single-bulb black garlic that is egual to 06704. The content of L-Arginine compounds in single garlic is greater than that of a single black garlic. L-Arginine is a semi essential amino acid and has a function in arterial vascular relaxation and improves blood flow. Single-bulb black garlic was produced from ordinary single-bulb garlic clove by process from maillard browning at temperature at 700C and 95Y of humidity controlled room for a month. It is known that single-bulb black garlic has benefits as antidiabetes, uric acid, cholesterol, hypertension, endurance and others. This study aims to determine the content of L-Arginine compound on single-bulb garlic and single-bulb black garlic by using HPLC (High Performance Liguid Chromatography)method.The mobile phase used consists of buffer A and buffer B. Buffer A consists of Na-Acetate (pH 6.5), Na-EDTA, Methanol, and Tetrahidrofuran. While B buffer consists of Methanol and Water Pro Injection. Thermo Scientific Column ODS-2 Hyersil C18, flow rate 1 ml / min, using Flouresensi detector with 350 nm wavelength. Based on the results obtained L-Arginine compound contained in a single-bulb garlic of 2.504 while for single-bulb black garlic that is egual to 06704. The content of L-Arginine compounds in single garlic is greater than that of a single black garlic.